Osteochondroma of the Distal Femur in Young Patient: An Oncology Case Report - Sandiwidayat, Komang Septian (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Osteochondroma is the most common primary bone tumor manifested as a painless, slow-growing mass. Apart from its asymptomatic manifestations, the tumor is malignant potential so appropriate management needs to be acknowledged. The aim of this study is to discuss the possible clinical findings for diagnosing with managing this rare case properly, which may provide a good outcome for this patient.Case Presentation: A 17-year-old male presented with a chief complaint of a slow-growing lump on the back of his right thigh. On physical examination, a 7 cm x 6 cm mass with mild tenderness was found during palpation. Based on these clinical and imaging findings, we informed and gained consent from the patient for surgery followed by a histopathology examination. The histopathology examination confirmed osteochondroma in the right distal femur.Results: Surgery was performed to curatively remove the tumor, followed by a histopathological examination which confirmed the diagnosis of osteochondroma. One week after the surgery, the post-surgical wound care was performed showing an excellent result, without any signs of infection or complications.Conclusion: Typical manifestation of painful osteochondromas may be associated with mechanical compression to the surrounding nerve and vascular structures. Surgical excision is an appropriate management approach to provide consistent relief of pain and deformity in osteochondroma case.Keywords: arteriovenous malformations, CT scan, rare case, embolizationCorrespondence: Komang Septian Sandiwidayat. Oncology Division, Department of Orthopaedic & Traumatology, Sanglah General Hospital, Faculty of Medicine, Udayana University, Bali, Indonesia. Email: drseptianortho@gmail.com. +62-821-4725-2042.Indonesian Journal of Medicine (2022), 07(01): 82-88https://doi.org/10.26911/theijmed.2022.07.01.09